Answer:
a). 8(x + a)
b). 8(h + 2x)
Step-by-step explanation:
a). Given function is, f(x) = 8x²
For x = a,
f(a) = 8a²
Now substitute these values in the expression,
= ![\frac{8x^2-8a^2}{x-a}](https://tex.z-dn.net/?f=%5Cfrac%7B8x%5E2-8a%5E2%7D%7Bx-a%7D)
= ![\frac{8(x^2-a^2)}{(x-a)}](https://tex.z-dn.net/?f=%5Cfrac%7B8%28x%5E2-a%5E2%29%7D%7B%28x-a%29%7D)
= ![\frac{8(x-a)(x+a)}{(x-a)}](https://tex.z-dn.net/?f=%5Cfrac%7B8%28x-a%29%28x%2Ba%29%7D%7B%28x-a%29%7D)
= 8(x + a)
b).
= ![\frac{8(x+h)^2-8x^2}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B8%28x%2Bh%29%5E2-8x%5E2%7D%7Bh%7D)
= ![\frac{8(x^2+h^2+2xh)-8x^2}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B8%28x%5E2%2Bh%5E2%2B2xh%29-8x%5E2%7D%7Bh%7D)
= ![\frac{8x^2+8h^2+16xh-8x^2}{h}](https://tex.z-dn.net/?f=%5Cfrac%7B8x%5E2%2B8h%5E2%2B16xh-8x%5E2%7D%7Bh%7D)
= (8h + 16x)
= 8(h + 2x)
Answer:
The answer to your question is y = 2x + 11
Step-by-step explanation:
Data
Original line y = -(1/2)x + 5
Point (-4, 3)
Process
1.- Get the slope of the new line
- Slope of the original line = -1/2
If the lines are perpendicular, the slopes must be reciprocal
-1/2 reciprocal = 2
2.- Get the equation of the new line
y - y1 = m(x - x1)
y - 3 = 2(x + 4)
- Simplification
y - 3 = 2x + 8
- Solve for y
y = 2x + 8 + 3
y = 2x + 11
Answer:
where is the question
have a good day :)
Step-by-step explanation:
Answer:
15.20,15.50
Step-by-step explanation:
Answer:
0.635
Step-by-step explanation:
1/4 x 2.54 = 0.635
:)